The Effect of Picture-Cued Task towards Students’ Motivation in Learning Writing - Warih Astuti; Taufik Suadiyatno (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study intended to find out the effect of Picture-Cued Task towards Students’ Motivation in Learning Writing at SMPN 3 Lingsar in the academic year 2018/2019. The population of the second grade of SMPN 3 Lingsar was 120 students and the researchers took VIII-B class as an Experimental group and VIII-D as a Control group. The Experimental group was treated by Picture-Cued Task and the Control group was treated by Mind Mapping. The instruments that were used to collect the data were tests and questionnaires. The data was analyzed by using Quantitative research and the way researchers analyzed the data was by; scoring, percentile meanings, and impacts. The Quantitative Data showed that the students were able to arrange their grammar and vocabularies well when making short sentences through Picture-Cued Task. Those students were enthusiastically joined the class even though they were wondering what to do with pictures. In Quantitative Data, the researchers found; Mean = 26,07, Median = 25, Mode = 20 and Standard Deviation = 6,434. The t-test score was 6,392 and the t-table was 1,67 in significance level 0,05 with the degree of freedom 54, therefore, the score of the t-test is higher than the t-table. Based on the data finding and discussion, it can be concluded that the use of Picture-Cued Task has a positive effect to motivate students in learning writing.